Effect of methyl acetoacetate as a potential cold flow improver for biodiesel. Issue 1 (2nd January 2017) - Lian, Xiang; Xue, Yuan; Xu, Guangwen; Zhao, Zhicheng; Sheng, Han; Lin, Hualin
ABSTRACT: This investigation was conducted to determine the cold flow properties of waste cooking oil biodiesel with methyl acetoacetate (MAA) as a potential flow improver. Now, 0.0 vol%, 2.5 vol%, 5.0 vol%, 7.5 vol%, 10 vol%, 15 vol%, and 20 vol% MAA were added to study the effects on the cold flow properties of waste cooking oil biodiesel. The results indicated that the filter plugging point, pour point (PP), and cold point (CP) were decreased by 5°C, 5°C, and 7°C, respectively, after being treated with 20 vol% MAA. Other fuel properties were also determined and compared with ASTM D6571. Additionally, the performance mechanism was explored by differential scanning calorimetry and polarizing microscopy.